Sericin A Boon to Medical and Dental doctors – A Review - Devi, Devarathnamma MV; Bhat, Geeta; Kudva, Praveen (International Journal of Clinical and Biomedical Research, 2023)
Silk sericin is a natural polymer produced by the silkworm, Bombyx mori, which surrounds and keeps together two fibroin filaments in silk thread used in the cocoon. The recovery and reuse of sericin usually discarded by the textile industry not only minimizes environmental issues but also has a high scientific and commercial value. The physicochemical properties of the molecule are responsible for numerous applications in biomedicine and are influenced by the extraction method and silkworm lineage, which can lead to variations in molecular weight and amino acid concentration of sericin. The presence of highly hydrophobic amino acids and their antioxidant potential make it possible for sericin to be applied in the food and cosmetic industry. The moisturizing power allows indications as a therapeutic agent for wound healing, stimulating cell proliferation, protection against ultraviolet radiation, and formulating creams and shampoos. The antioxidant activity associated with the low digestibility of sericin expands the application in the medical field, such as antitumour, antimicrobial and anti-inflammatory agent, and anticoagulant, acts in colon health, improving constipation and protecting the body from obesity through improved plasma lipid profile. In addition, the properties of sericin allow its application as a culture medium and cryopreservation, in tissue engineering and for drug delivery, demonstrating its effective use, as an important biomaterial. The present review on sericin describes its properties and application in various fields. Keywords: Silk, sericin, biomedical, dental, biomaterial, biodegradable, biocompatible.